Effect of Sequential Inoculation of Tetragenococcus halophilus and Wickerhamomyces anomalus on the Flavour Formation of Early-Stage Moromi Fermented at a Lower Temperature - Xinzhi Li; Xinyu Xu; Changzheng Wu; Xing Tong; Shiyi Ou (Foods, 2023)
Microbial inoculation in moromi fermentation has a great influence on the physicochemical and flavour properties of soy sauces. This work investigated the effect of inoculating Tetragenococcus halophilus and Wickerhamomyces anomalus on the flavour formation of early-stage moromi (30 days) fermented at a lower temperature (22 °C) by determining their physicochemical and aroma changes. The results showed that single yeast or LAB inoculation increased the production of amino nitrogen, lactic acid and acetic acid, as well as free amino acids and key flavour components. Particularly, the sequential inoculation of T. halophilus and W. anomalus produced more free amino acids and aromatic compounds, and there might be synergistic effects between these two strains. More characteristic soy sauce flavour compounds, such as benzaldehyde, HEMF, guaiacol and methyl maltol were detected in the sequentially inoculated moromi, and this sample showed higher scores in savoury, roasted and caramel intensities. These results confirmed that sequential inoculation of T. halophilus and W. anomalus could be a choice for the future production of moromi with good flavour and quality under a lower temperature.